Well Presence, Well Performance: The Effect of Online Presence on Indonesian Remote Employees’ Performance through Workplace Well-Being - Febriawan, Iqbal Maesa (UI Scholars Hub, 2024)
Accelerated by the COVID-19 pandemic and driven by technological advances as well as changing attitudes toward traditional office environments, the workplace landscape has experienced a rapid shift toward remote work. Regardless of urban employees’ interest in remote work, studies have yet to explore the impact of online presence on employee performance as mediated by workplace well-being. A total of 132 private and government employees completed three questionnaires. The results supported the hypothesis that workplace well-being mediates the effect of online presence on performance. The findings also suggest that employees with stronger online presence tend to have better workplace well-being, which then leads to higher performance levels. These results shed light on the importance of managing online presence in remote work settings. Organizations must recognize the impact of online presence on their employees’ well-being and ultimately their performance by considering policies and their enablers to support presence at the virtual workplace.